Are parents’ willing to vaccinate their children against COVID-19? A qualitative study based on the Health Belief Model - Mona T. Rajeh; Deema J. Farsi; Nada J. Farsi; Hala H. Mosli; Mohammed H. Mosli (Human Vaccines & Immunotherapeutics, 2023)
In response to the COVID-19 pandemic, several countries have started implementing voluntary or involuntary mass vaccination programs. Although vaccine acceptance is high among adults, uncertainty about whether to vaccinate children against COVID-19 remains a controversial theme. To date, few qualitative studies have explored parents’ views on this topic. A qualitative descriptive study design was used to collect data and individual in-depth interviews were conducted with 50 parents in the Makkah region of Saudi Arabia. The Health Belief Model (HBM) was used as a guide in developing the interview guide. Each question was related to a construct of the HBM. The data were then analyzed using thematic content analysis and interpreted using NVivo software. Two major themes emerged: motivation to vaccinate children, which was influenced by perceived benefits, perceived severity, perceived suitability, collective responsibilities, confidence, and cues to action; and barriers to vaccination in children, which included complacency, rapid vaccine development, and uncertainty about the long-term side effects of the vaccine. The findings of this study revealed that the public is not sufficiently informed about the efficacy or side effects of the COVID-19 vaccine, increasing the awareness of which will help parents make informed decisions regarding vaccinating their children and potentially increase vaccine acceptance.